2018
DOI: 10.12968/bjom.2018.26.8.523
|View full text |Cite
|
Sign up to set email alerts
|

Student midwives' education needs and their experience of attending a bereavement education workshop

Abstract: Background Clinical training should be efficient, intellectually rigorous, and integrated into practice. This interactive workshop was developed to support student midwives in bereavement care. Aims To improve student midwives' confidence in providing bereavement care to parents after pregnancy loss and perinatal death. Methods Two focus groups were held, where students' (n=12) discussed their experiences of attending the workshop, barriers and facilitators to gaining confidence, and any further education need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The research found that medical quality is the core of hospital management. In the process of hospital development, the brand and performance of a hospital are of great significance to the survival and development of the hospital [ 16 ]. Use the PDCA cycle to establish a complete medical quality management system, formulate countermeasures for the problems found in the evaluation of the PDCA cycle, and establish the inspection standards.…”
Section: Related Workmentioning
confidence: 99%
“…The research found that medical quality is the core of hospital management. In the process of hospital development, the brand and performance of a hospital are of great significance to the survival and development of the hospital [ 16 ]. Use the PDCA cycle to establish a complete medical quality management system, formulate countermeasures for the problems found in the evaluation of the PDCA cycle, and establish the inspection standards.…”
Section: Related Workmentioning
confidence: 99%
“…Together, midwives and nurses form the largest group of professionals employed in health care services and potentially play an important role in bereavement care worldwide [9,10]. When the pregnancy ends with negative pregnancy outcomes, nursing professionals have the responsibility to help bereaved parents deal with this cruel reality; however, the majority of midwives and nurses are not prepared for this incident and lack the confidence to provide bereavement care [11][12][13]. Specifically, they reported inadequate counselling and communication skills [14].…”
Section: Introductionmentioning
confidence: 99%
“…Most nursing professionals felt unprepared and lacked the confidence to provide perinatal bereavement care 24 25. They do not know how to communicate with the women and their families 26 27.…”
Section: Introductionmentioning
confidence: 99%